Pengaruh Penguasaan Konsep Bangun Datar Dan Konsep Aljabar Terhadap Kemampuan Menyelesaiakan Soal-Soal Bangun Ruang Sisi Datar - Meilani, Lutfia; Legowati, Endang; Sumartono, Sumartono (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2017)
The purpose of this research is to 1) Knowing whether or not the influence of mastery of the concept of flat wake up to the ability to solve the problems of building the flat side space of students of grade VIII SMP Negeri 1 Kunjang, 2) Knowing there or not the influence of mastering the concept of algebra on the ability to solve the problems of building flatspace on the students of grade VIII SMP Negeri 1 Kunjang, 3) Knowing whether or not the influence of mastery of the concept of wake-up and algebraic concept of the ability to solve the problem of building the flat- side room of the class VIII SMP Negeri 1 Kunjang. This is acomparative causal study. Members of the population of 218 students. Technique of sampling technique of random sampling. Samples were taken about 13% of the total population of 42 students. Technique of collecting data using test method and method of documentation. Data analysis technique using multiple linear regression analysis. The results of the analysis together obtained Fhitung of 78.929> Ftabel=3.24 and Asymp probability value. Sig0,0000<a(0.05). This means there is asignificant influence between the mastery of the concept of wake-up and algebraic concept of the ability to solve the problem of building flat side space with the coefficient of determination of . Partially, the mastery of the concept of wake up to the ability to solve the problem of building the flat side space is shown by the result ofttes to btained thitung=11,029>ttable =2.02 and Asymp probability value. Sig is 0,0000 <a(0,05) with coefficient of determination . Mastery of algebraic concept on the ability to solve the problem of building flat side space is shown by ttest result obtained tcount= 8,793>ttable=2.02 and Asymp Sig value of 0,0000<a(0,05) with coefficient of determination. Keywords: Two-dimentionalfigure, Algebra, Geometry